Rock mechanics and engineering for the Klein Matterhorn glacier paradise (Zermatt, Switzerland). Issue 1 (August 2021) - Dalban, P; Haas, R; Lauber, M; Naterop, D
Abstract: The Alpin X project is carried out by the Zermatt Bergbahnen AG and aims at establishing a touristic link between Zermatt in Switzerland and Cervinia in Italy while facilitating access to the top of the Klein Matterhorn. This very challenging project is based on the construction of two new modern cableways joining each other at adjacent arrival stations founded in the 50-70° steep west face of the Klein Matterhorn, at 3'820.5 m a.s.l. Due to the steepness of the slope, construction works require extensive excavation and stabilization of the serpentinite bedrock and consequently to address various problematics related to superficial and shallow rock instabilities inside and outside the construction area. Moreover, the predominance of permafrost conditions required to adapt the techniques for the execution. While the first cableway from the north-side has been operational since winter 2018/2019, the second from the south is still under construction and will open in winter 2021/2022.